Implementasi Sensor Inframerah Sebagai Switch Pada Sensor AMG8833 Dan Pompa Air Di Smart Security COVID-19 - Lafinal Yak Mahdiantoro; Rahmat Hidayat; Lela Nurpulela (Universitas Islam Lamongan, 2021)
Covid-19 is currently spreading throughout the world without exception in Indonesia. With this fact, the government recommends the public to maintain health protocols, especially in public places as a form of resistance to COVID-19 so that the transmission rate can be suppressed. one of them is to keep a distance and avoid physical contact with other people and object surfaces. The Smart Security COVID-19 designed to be able to detect temperature and spray disinfectant liquid automatically without need for physical contact. Infrared sensor that functions as a data sender when a user approaches the device, which is then sent to Arduino UNO for processing the processed data and will be sent to the AMG8833 temperature sensor and relay where the AMG8833 temperature sensor functions as a temperature reader and the relay functions to activate the pump to spraying disinfectant liquid.